2003
DOI: 10.1126/science.1086560
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Active Force Generators Controls Mitotic Spindle Position

Abstract: During unequal cell divisions a mitotic spindle is eccentrically positioned before cell cleavage. To determine the basis of the net force imbalance that causes spindle displacement in one-cell Caenorhabditis elegans embryos, we fragmented centrosomes with an ultraviolet laser. Analysis of the mean and variance of fragment speeds suggests that the force imbalance is due to a larger number of force generators pulling on astral microtubules of the posterior aster relative to the anterior aster. Moreover, activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
359
6
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 352 publications
(393 citation statements)
references
References 24 publications
27
359
6
1
Order By: Relevance
“…The laser ablation experiments were performed using a highly focused ultraviolet laser beam and observed using differential interference contrast (DIC) and spinning-disk microscopy as described 22 , except that a Melles Griot ArIon Laser (488 nm, 100 mW) laser was used for fluorescence imaging. All ablations were performed in DIC optics.…”
Section: Methodsmentioning
confidence: 99%
“…The laser ablation experiments were performed using a highly focused ultraviolet laser beam and observed using differential interference contrast (DIC) and spinning-disk microscopy as described 22 , except that a Melles Griot ArIon Laser (488 nm, 100 mW) laser was used for fluorescence imaging. All ablations were performed in DIC optics.…”
Section: Methodsmentioning
confidence: 99%
“…Such experiments illustrate the existence of a mechanical link between the spindle and specialized cortical regions [4,5]. Laser microsurgery experiments in Fusarium solani or C. elegans suggested that this link corresponds to astral microtubules connecting the spindle poles with the cell cortex [6,7,8,9,10 ]. Although not the focus of this review, there are instances where pulling forces are exerted along the length of astral microtubules instead of at their plusend located at the cell cortex [11,12,13].…”
mentioning
confidence: 94%
“…First, mechanical material properties play a key role in the control of numerous cellular processes such as cell shape changes [1], cell locomotion [2], adhesion [3] or cell division [4] by mechanical forces. Second, local forces can control the cellular architecture in a subtle way, for instance through the activation of small GTPases of the rho-family [5] which can result in rapid (sub-second) reorganizations of the actin network [6], including the formation of stress fibres [7], the activation of micro-muscles or the growth of cellular protrusions, such as philipodia [8] or axons [9].…”
Section: Introductionmentioning
confidence: 99%